Observations on Texas hypoxylons, including two new Hypoxylon species and widespread environmental isolates of the H. croceum complex identified by a polyphasic approach. (3rd September 2019) - Sir, Esteban B.; Becker, Kevin; Lambert, Christopher; Bills, Gerald F.; Kuhnert, Eric
ABSTRACT: Two new species and a new combination of Hypoxylon from Texas were identified and described based on morphological, multigene phylogenetic (ITS [nuc rDNA internal transcribed spacer region ITS1-5.8S-ITS2], 28S [5′ 1200 bp of nuc 28S rDNA], RPB2 [partial second largest subunit of the DNA-directed RNA polymerase II], TUB2 [partial β-tubulin] ), and chemotaxonomic data. Hypoxylon olivaceopigmentum is characterized by its pulvinate to glomerate stromata, olivaceous KOH-extractable pigments, equilateral ascospores, and indehiscent perispore. Hypoxylon texense can be distinguished from morphologically similar species by its rust to dark brick KOH-extractable pigments and the high-performance liquid chromatography (HPLC) profile of its stromatal secondary metabolites. Hypoxylon hinnuleum is proposed as the sexual morph of Nodulisporium hinnuleum, featuring dark vinaceous glomerate stromata with dark brick KOH-extractable pigments composed of cohaerin-type azaphilones and smooth equilateral ascospores with indehiscent perispore. Based on these diagnostic characters, H. hinnuleum forms a complex with H. croceum and H. minicroceum . More than 50 ITS sequences with high identity originating from North American and East Asian environmental isolates formed a well-supported clade with the type of N. hinnuleum, demonstrating the widespread distribution of the species complex. In addition, updated descriptions and comprehensive illustrations with detailed information on the diagnostic features of H. fendleri and H. perforatum are provided. The multilocus phylogenetic reconstruction of Hypoxylon supported the status of the new species and broadened the knowledge about intergeneric relationships.